Quality Management in Educational Institutions - Choubey, Nitin S.; Sambare, Santosh S. (Journal of Engineering Education Transformations, 2007)
Quality is defined as combination of the various attributes desired from any entity. Quality of teaching can be measured, indirectly either through the presence of professional attributes, including skills, knowledge, qualifications and professional learning of the tutor or through their student s acceptability. Paper attempts to identify factors that are most closely associated with positive outcomes and determines how these attributes and capabilities can be developed, sustained and communicated. It also emphases on the improvements in students' social and academic outcomes, teacher performance and community relations can also be linked to quality of leadership although the relationship between outcomes and the role of the Leader is less direct. Raising the quality of teaching is an important focus for education and training policy.